2017
DOI: 10.1038/s41598-017-08377-0
|View full text |Cite
|
Sign up to set email alerts
|

Combination of chemical fingerprint and bioactivity evaluation to explore the antibacterial components of Salvia miltiorrhizae

Abstract: The aim of this study was to explore the possible antibacterial components of Salvia miltiorrhizae on Pseudomonas aeruginosa using a combination of chemical fingerprint and bioactivity evaluation. The chemical fingerprints of 32 batches of S. miltiorrhizae samples from different sources were developed using high-performance liquid chromatography with diode array detection, and then were evaluated by similarity analysis and hierarchical clustering analysis. Anti-P. aeruginosa activity was determined by microcal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…There is a direct relationship between the content of rutin and its ability to inhibit S. suis biofilm. Kong et al (2017) also reported that the most abundant compounds might not be the major contributors to antibacterial activity. This is also in tandem with our study.…”
Section: Discussionmentioning
confidence: 99%
“…There is a direct relationship between the content of rutin and its ability to inhibit S. suis biofilm. Kong et al (2017) also reported that the most abundant compounds might not be the major contributors to antibacterial activity. This is also in tandem with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Fingerprint-activity relationship modeling of TCM is based on the guidance of TCM theory. The fingerprints and pharmacodynamics of TCMs, which are correlated by chemometric models, establish a comprehensive evaluation system for revealing the material basis of the pharmacodynamics of TCMs 46 . This has been one of the approaches used for predicting active ingredients and performing quality control in natural products.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, ReliefF was then applied for preliminarily ranking and selecting the peaks associated with anti-diabetes activities. Multiple prospective studies have established different chemometric multivariate techniques, such as partial least squares regression (PLSR) [46], multiple linear regression analysis [47], and BP-ANN [41], etc., in the screen of bioactive compounds. Due to the superior performance, and its explanation capabilities for complex interactions between input and target variables, BP-ANN model was established and optimized to evaluate the correlations between selected peak data and the bioactivities data.…”
Section: Discussionmentioning
confidence: 99%